1992
DOI: 10.1073/pnas.89.11.4781
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity changes and hydrophobic interactions in the binding of FK506 and rapamycin to the FK506 binding protein.

Abstract: Hydrophobic interactions, believed to be important determinants of the stability of many protein structures, multisubunit protein complexes, and protein/ligand complexes, may be considered to be the result of two component interaction processes: the removal of nonpolar groups from water (hydration) and the packing of these groups within proteins or protein complexes. Early studies by Kauzmann (8) and Tanford (9) emphasized the similarities of protein unfolding and the transfer of nonpolar substances from water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 26 publications
6
45
0
2
Order By: Relevance
“…22 The Fab-YADS1 interaction is somewhat less typical, as there is a very favorable DH value opposed by a large, unfavorable DS, with a more negative DC p value. This pattern of thermodynamic parameters has been observed in other protein-protein interactions, for example in the binding of tissue factor to coagulation factor VIIa.…”
Section: Resultsmentioning
confidence: 98%
“…22 The Fab-YADS1 interaction is somewhat less typical, as there is a very favorable DH value opposed by a large, unfavorable DS, with a more negative DC p value. This pattern of thermodynamic parameters has been observed in other protein-protein interactions, for example in the binding of tissue factor to coagulation factor VIIa.…”
Section: Resultsmentioning
confidence: 98%
“…We previously quantified the heat capacity change with temperature (ΔC p = dΔH°/dT) for the binding of GDP and GTP to IF2 or EF-G. 14,15 Using the linear relationship between ΔC p and change in solvent-accessible area, 29 we interpreted the data as structural rearrangements induced by G nucleotide binding. We suggested that there is no conformational change in EF-G upon GDP binding, since the heat capacity change is numerically small [ΔC p (GDP) = − 21 ± 5 cal mol − 1 K − 1 ].…”
Section: Comparative Thermodynamics Of Guanine Nucleotide Binding To mentioning
confidence: 99%
“…For instance, a large negative ΔC p signal is characteristic of a large reduction in the solventaccessible area of a protein, typical of peptide chain folding or protein-protein complex formation. 32,33 The heat capacity change has been related to the change in solvent-accessible area through the empirical expression ΔC p = 0.27ΔA aromatic + 0.4ΔA nonaromatic , where ΔA aromatic and ΔA nonaromatic are the protected areas (in Å 2 ) due to aromatic and nonaromatic amino acid residues, respectively. 33 From the slopes of the two straight lines in Fig.…”
Section: Structural and Functional Implications For If2 Gtpase Cyclementioning
confidence: 99%
“…32,33 The heat capacity change has been related to the change in solvent-accessible area through the empirical expression ΔC p = 0.27ΔA aromatic + 0.4ΔA nonaromatic , where ΔA aromatic and ΔA nonaromatic are the protected areas (in Å 2 ) due to aromatic and nonaromatic amino acid residues, respectively. 33 From the slopes of the two straight lines in Fig. 2a, we have estimated the heat capacity changes (constant in the temperature interval 4-25°C) upon GTP (ΔC p GTP = −868 cal mol − 1 ) and GDP (ΔC p GTP = −577 cal mol − 1 ) binding to IF2.…”
Section: Structural and Functional Implications For If2 Gtpase Cyclementioning
confidence: 99%